2005
DOI: 10.1093/nar/gni073
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of scanning force microscopy images of protein-induced DNA bending using simulations

Abstract: Bending of DNA is a feature essential to the function of many DNA-binding proteins. Bending angles can be estimated with a variety of techniques, but most directly from images obtained using scanning force microscopy (SFM). Direct measurement of the bending angle using a tangent method often produces angles that deviate significantly from values obtained using other techniques. Here, we describe the application of SFM in combination with simulations of DNA as a means to estimate protein-induced bending angles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
34
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 36 publications
5
34
0
Order By: Relevance
“…As a result of crosssectional analysis of the scIHF2 that bound with IHF box containing DNA, the three-dimensional geometry of scIHF2 was similarly shaped (height=1.15 nm, width= 15 nm) in the previous reports (Fig. 4c) [24,25].…”
Section: Evaluation Of Dna Binding and Bending Capability Of Scihf2 Usupporting
confidence: 66%
See 1 more Smart Citation
“…As a result of crosssectional analysis of the scIHF2 that bound with IHF box containing DNA, the three-dimensional geometry of scIHF2 was similarly shaped (height=1.15 nm, width= 15 nm) in the previous reports (Fig. 4c) [24,25].…”
Section: Evaluation Of Dna Binding and Bending Capability Of Scihf2 Usupporting
confidence: 66%
“…Following the theory of DNA geometry, 100 bp of (n=10, approximately 34 nm) linker DNA was designed for fabrication of DNA actuator. This shortening of linker DNA was caused by wrapping around scIHF2 and bent, thus reversing the direction of the helix axis within the short length [24,25].…”
Section: Evaluation Of Dna Binding and Bending Capability Of Scihf2 Umentioning
confidence: 99%
“…Interestingly, recent findings demonstrated that an HU mutant acquired DNA condensation activity as a result of gaining the oligomerization activity (73). This proposed mechanism is clearly distinct from other DNA-associating proteins, such as HU (24), SMC (74), IHF (75) and FIS (76), which are proposed to function through a wrapping mechanism (48). …”
Section: Discussionmentioning
confidence: 81%
“…These methods have been exploited for different purposes, as the experimental validation of models for DNA adsorption and bending12456789 or the correlation of DNA shape and flexibility to melting10, ligand interactions111213, replication14, genomic packaging and transcription regulation1516. The wide applicability of DNA conformational studies demands simple experimental methods, characterized by a few processing steps for specimen preparation and minimum experimental bias on curvature and flexibility measurements.…”
mentioning
confidence: 99%